An assessment of growth indicators and intricacies of Udyam entities in the post-pandemic era - Vishnu Prasad C; Ramaprabha D (The Scientific Temper, 2024)
Udyam registered entities constitute the predominant share of budding business units in India. Udyam registration has in a sense, revolutionized the formalization of the small business sector in India by way of undertaking unprecedented measures and efforts to bring informal units to the ambit of incorporation, especially at a time when these units were trying to insulate themselves against economic shocks caused by the Covid-19 pandemic. Three years down the line, the study aims to have a look at service enterprises, consisting of both trading and non-trading units, to measure their business growth and performance with reference to certain indicators, viz., sales, profits, assets, capital and customer base. An attempt is made to regress profits with the other key indicators. The study also makes a note of the directional relationship that is possessed by each of these indicators with the other parameters. It is observed that building wealth in the form of better assets should be the prime focus of small units, as they possess very good statistical association with returns. Also, sensitizing MSMEs on the role of Udyam, especially in terms of solving and easing out challenges associated with financing, can be instrumental.